Diversity and community structure of social wasps (Hymenoptera: Vespidae) in three ecosystems in itaparica island, Bahia State, Brazil - Santos, Gilberto M. de M. (2007)
We studied the structure and composition of communities of social wasps associated with the three insular ecosystems: mangrove swamp, the Atlantic Rain Forest and the 'restinga'- lowland sandy ecosystems located between the mountain range and the sea. Three hundred and ninety-one nests of 21 social wasp species were collected. The diversity of wasps found in each ecosystem was significantly correlated to the diversity of vegetation in each of the three physiognomies, (r2 = 0.85; F(1.16) = 93.85; P < 0. 01). The Tropical Atlantic Forest physiognomy had higher species richness (18 species), followed by the restinga (16 species) and the mangrove (8 species) ecosystems.